Alopecia in a Viable Phospholipase C Delta 1 and Phospholipase C Delta 3 Double Mutant - Runkel, Fabian; Hintze, Maik; Griesing, Sebastian; Michels, Marion; Blanck, Birgit; Fukami, Kiyoko; Guénet, Jean-Louis; Franz, Thomas (PLOS ONE, 2012)
Background Inositol 1,4,5trisphosphate (IP3) and diacylglycerol (DAG) are important intracellular signalling molecules in various tissues. They are generated by the phospholipase C family of enzymes, of which phospholipase C delta (PLCD) forms one class. Studies with functional inactivation of Plcd isozyme encoding genes in mice have revealed that loss of both Plcd1 and Plcd3 causes early embryonic death. Inactivation of Plcd1 alone causes loss of hair (alopecia), whereas inactivation of Plcd3 alone has no apparent phenotypic effect. To investigate a possible synergy of Plcd1 and Plcd3 in postnatal mice, novel mutations of these genes compatible with life after birth need to be found. Methodology/Principal Findings We characterise a novel mouse mutant with a spontaneously arisen mutation in Plcd3 (Plcd3mNab) that resulted from the insertion of an intracisternal A particle (IAP) into intron 2 of the Plcd3 gene. This mutation leads to the predominant expression of a truncated PLCD3 protein lacking the N-terminal PH domain. C3H mice that carry one or two mutant Plcd3mNab alleles are phenotypically normal. However, the presence of one Plcd3mNab allele exacerbates the alopecia caused by the loss of functional Plcd1 in Del(9)olt1Pas mutant mice with respect to the number of hair follicles affected and the body region involved. Mice double homozygous for both the Del(9)olt1Pas and the Plcd3mNab mutations survive for several weeks and exhibit total alopecia associated with fragile hair shafts showing altered expression of some structural genes and shortened phases of proliferation in hair follicle matrix cells. Conclusions/Significance The Plcd3mNab mutation is a novel hypomorphic mutation of Plcd3. Our investigations suggest that Plcd1 and Plcd3 have synergistic effects on the murine hair follicle in specific regions of the body surface.